Codinaea linzhiensis sp. nov. (Chaetosphaeriales, Sordariomycetes), a freshwater hyphomycete from Qinghai–Xizang Plateau, China - Mu, Li-Heng; Xu, Rong-Ju; Luo, Zong-Long; Zhao, Qi (Phytotaxa, 2026)
During an investigation of lignicolous freshwater fungi on the Qinghai–Xizang Plateau, two hyphomycetous isolates were obtained from submerged wood in freshwater habitats. Morphological studies combined with multi-gene phylogenetic analyses based on ITS, LSU, and TEF1-α sequences revealed that the isolates belong to the genus Codinaea (Chaetosphaeriaceae). Based on both molecular and morphological evidence, a new species, C. linzhiensis, is introduced and described herein from its asexual morph. Detailed morphological descriptions and justifications for the establishment of this new species are provided. This discovery further expands the known diversity of freshwater fungi on the Qinghai–Xizang Plateau.